HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TERHADAP KEPATUHAN ANTENATAL CARE DI RUMAH SAKIT ARSANI SUNGAILIAT TAHUN 2024 - Rahayu, Elis Gustian (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
This study aims to analyze the relationship between knowledge and attitudes of pregnant women towards Antenatal Care (ANC) compliance at Arsani Sungailiat Hospital in 2024. Using a cross-sectional design, this study involved 95 third-trimester pregnant women. Data were collected through validated questionnaires and analyzed using chi-square tests. Results showed that 70.5% of respondents had good knowledge, 74.7% had positive attitudes, and 76.8% were compliant with ANC. Bivariate analysis revealed significant relationships between knowledge (p=0.007; POR=4.275; 95% CI=1.563-11.689) and attitudes (p=0.001; POR=6.100; 95% CI=2.150-17.306) with ANC compliance. These findings emphasize the importance of health education and fostering positive attitudes in improving ANC compliance. Research implications include strengthening educational programs, developing effective communication strategies, and improving ANC service quality. Further research with longitudinal designs and more diverse data collection methods is recommended for a more comprehensive understanding.